Bioproduction of a novel sugar 1-deoxy-L-fructose by Enterobacter aerogenes IK7; isomerization of a 6-deoxyhexose to a 1-deoxyhexose - Gullapalli, P; Shiji, T; Rao, D; Yoshihara, A; Morimoto, K; Takata, G; Fleet, G; Izumori, K (2007)
1-Deoxy-l-fructose, a very rare monosaccharide, was produced by hydrogenation of 6-deoxy-l-mannose (l-rhamnose)-the only cheaply available deoxy sugar-to 1-deoxy-l-mannitol (l-rhamnitol) followed by oxidation with Enterobacter aerogenes IK7. The entire procedure was conducted in water and shows the power of green environmentally friendly chemistry combined with biotechnology in the preparation of new monosaccharides with potential for novel bioactive properties or alternative foodstuffs; the reactions here are reported on a multigram scale but would be reproducible on a very large scale. © 2007.